Social networking sites use and life satisfaction. A quantitative study on older people living in Europe. Issue 1 (1st January 2021) - Gaia, Alessandra; Sala, Emanuela; Cerati, Gabriele
ABSTRACT: The European ageing population poses unprecedented challenges to society as a whole. Social Networking Sites might be important tools to boost older people's well-being, strengthening and creating social connections in old age. Despite of its potentialities, there is relatively little knowledge on the impact of SNS use on older people's well-being, especially in Europe. Our study investigates the relationship between SNS use and life satisfaction (a key measure of well-being) in old age. We use data from the 2017 Standard Eurobarometer 88 survey, performing a set of multilevel regression models. To fully understand the specificity of the relationship between SNS use and life satisfaction in old age population, we perform a multi-cohort analysis. We find a positive association between SNS use and life satisfaction in old age, association that persists after controlling for a number of possible confounding effects.